Frontal Lobe Atrophy in Depression after Stroke - W. K. Tang; Y. K. Chen; J. Y. Lu; V. C. T. Mok; Winnie C. W. Chu; Gabor S. Ungvari; K. S. Wong (Stroke Research and Treatment)
Background. Frontal lobe atrophy (FLA) is associated with late life depression. However, the role that FLA plays in the development of depression after stroke (DAS) remains unknown. This study thus examined the association between FLA and DAS. Methods. A convenience sample of 705 Chinese patients with acute ischemic stroke admitted to the acute stroke unit of a university-affiliated regional hospital in Hong Kong participated in the study. A psychiatrist administered the Structural Clinical Interview for DSM-IV to all patients and made a diagnosis of DAS three months after the index stroke. Results. Eighty-five (12.1%) patients were diagnosed with DAS. In univariate analysis, the DAS patients were more likely to have severe FLA (14.1% versus 5.6%). Severe FLA remained an independent predictor of DAS in multivariate analysis, with an odds ratio of 2.6 (95% confidence intervals = 1.2–5.9). Conclusions. The results suggest that FLA may play a role in the pathogenesis of DAS, which supports the hypothesis that cumulative vascular burden may be important in predicting DAS. Further investigations are needed to clarify the impact of FLA on the clinical presentation, treatment response, and outcome of DAS in stroke survivors.